Virtual Professional Learning for School Teachers to Support Them in Online Environment - Singh, Balwant; Zamaletdinov, Radif; Kaur, Balwinder; Singh, Jaspal (Frontiers in Education, 2022)
In March 2020 World Health Organization (WHO) declared the coronavirus epidemic a pandemic and whole education system came to a standstill. An immediate transformation from offline mode to online mode of teaching learning was needed. Majority of teachers in India were not prepared for digital pedagogy. In spite of serious difficulties and deep-rooted traditional teaching and learning methods, they quickly involved themselves in their professional learning virtually and adopted the online teaching methods to keep the system going on. Thus, the present study is focused to find the answers of the questions emerged out of this situation such as (i) How teachers prepared themselves to come forward for gigantic initiative? (ii) How did they learn the digital online techniques? (iii) How the deficiencies of electronic gadgets like mobile phones, tablets etc. were arranged in short span of time and made available to all the stakeholders? This is a qualitative study using phenomenological enquiry as an approach, participants were selected with purposive sampling technique and data was collected through in-depth (semi-structured) interviews of 15 school teachers, 5 school heads and 5 block education mentors from Punjab state of India. The findings of the study indicated that with continuous motivation, school teachers took the initiative to come forward for digital teaching and learning. Some teachers out of firm professional commitment managed to pursue their professional learning mainly through their own efforts. Education Department also provided online crash courses to the teachers. Clusters of teachers having sound knowledge of technology collaboratively trained the teachers at block levels. Majority of teachers have their own gadgets but underprivileged sections were provided mobiles and tablets by government and non-government agencies. A quick shift to virtual professional learning resulted in significant improvements in learning outcomes of the students. Hence, the study will motivate the teachers of other states to pursue virtual professional learning to update themselves. It also suggests that teachers ought to be part of forums, interest groups and online professional communities to interact with peers and know how the rest of the world is doing with digital education.